Expert Angular - Nayrolles, Mathieu; Nayrolles, Mathieu; Gunasundaram, Rajesh; Rao, Sridhar (Packt Publishing, 2017)
Learn everything you need to build highly scalable, robust web applications using Angular release 4About This BookApply best practices and design patterns to achieve higher scalability in your Angular applicationsUnderstand the latest features of Angular and create your own componentsGet acquainted with powerful, advanced techniques in Angular to build professional web applicationsWho This Book Is ForThis book is for JavaScript developers with some prior exposure to Angular, at least through basic examples. We assume that you've got working knowledge of HTML, CSS, and JavaScript.What You Will LearnImplement asynchronous programming using AngularBeautify your application with the UI components built to the material design specificationSecure your web application from unauthorized usersCreate complex forms, taking full advantage of 2-way data bindingTest your Angular applications using the Jasmine and Protractor frameworks for better efficiencyLearn how to integrate Angular with Bootstrap to create compelling web applicationsUse Angular built-in classes to apply animation in your appIn DetailGot some experience of Angular under your belt? Want to learn everything about using advanced features for developing websites? This book is everything you need for the deep understanding of Angular that will set you apart from the developer crowd.Angular has introduced a new way to build applications. Creating complex and rich web applications, with a lighter resource footprint, has never been easier or faster. Angular is now at release 4, with significant changes through previous versions.This book has been written and tested for Angular release 4.Angular is a mature technology, and you'll likely have applications built with earlier versions. This book starts by showing you best practices and approaches to migrating your existing Angular applications so that you can be immediately up-to-date. You will take an in-depth look at components and see how to control the user journey in your applications by implementing routing and navigation. You will learn how to work with asynchronous programming by using Observables.To easily build applications that look great, you will learn all about template syntax and how to beautify applications with Material Design. Mastering forms and data binding will further speed up your application development time. Learning about managing services and animations will help you to progressively enhance your applications. Next you'll use native directives to integrate Bootstrap with Angular. You will see the best ways to test your application with the leading options such as Jasmine and Protractor.At the end of the book, you'll learn how to apply design patterns in Angular, and see the benefits they will bring to your development.Style and approachThis book provides comprehensive coverage of all aspects of development with Angular. You will learn about all the most powerful Angular concepts, with examples and best practices. This book is everything you need for the deep understanding of Angular that will set you apart from the developer crowd.